A Production and operations management study on Polymer Products Inc. - Concepcion, Tatiana Joy M. (College of Engineering, 2003)
Polymer Products Inc. is a leading manufacturer and supplier of polymer resins. Its products can be group into five main categories or product lines: vinylester resins, products pre-mixed with cobalt and styrene, raw blends, pre-mixed blends and polyester resin auxillaries. Though resins are grouped into different categories, they all undergo the same basic manufacturing processes. Differences only occur in the resin specifications, active ingredients, mixing times, batch sizes and type of packaging. In order to improve the production and operations system at Polymer Products, Inc., different areas of concern related to operations management -- namely, the design of goods, process strategy, quality management, workforce management, location and layout, capacity, and inventory, were evaluated and specific problems were identified for each. Using Streamline Diagnostic Diagram and Cause-and-Effect Charts (Ishikawa Diagrams), it was determined that the production problems currently experienced by the company can be attributed to those three root causes: (1) absence of a forecasting technique for demand, (2) non-implementation of aggregate planning, and (3) the present layout is not designed to minimize transportation delays between departments. Several forecasting models were evaluated for this study. Error analysis involved plotting of tracking signals against time and comparing them to predetermined limits. It was determined that the naive approach will yield the most accurate demand forecasts for all five product lines. For aggregate planning, the spreadsheet approach was recommended because of the ease of application in actual production systems. Based on the forecasts, sample production plans using pure chase demand and pure level capacity strategies were generated using the spreadsheet built by the group. To maximize the use and benefits of the recommended technique, the company must evaluate all possible strategies in order to determine the best alternative. The achievement of a successful plan will greatly depend of the resourcefulness and persistence of the company's production planner. Finally, the current layout was analyzed by constructing a Flow Diagram to depict the flow of materials, as well as a Load-Distance Matrix to detail the relative importance of each pair of departments between which materials flow. Using the insights gained from these techniques, a new layout was designed wherein all the temporary storage areas were situated in the original mixing area, and the repacking stations were moved to one side of the repacking area to make room for the relocated mixers. Meanwhile, the weighing station was placed between the storage shelves and the new repacking area. It was found that the new layout resulted in much shorter flows, and it significantly decreased costs by lessening transportation delays and reducing the need for lighting and ventilation in some areas of the plant.